Fast food: feasts in transition in the Late Neolithic to Early Bronze Age northern Aegean - Jordan, J.W. (2017)
Feasting is a central social practice in past societies, and exists in some form in almost every human society. The development of feasting in the northern Aegean Late Neolithic and Early Bronze Age is one of gradual, but visible change – set against the backdrop of wider social changes. Such changes in inter-personal feasting relations can shed light on socio-political development on a macro scale. Through several case studies, it is possible to examine the development of feasting in the northern Aegean, and through a comparative analysis consider the implications these developments have for, among other things, the creation of elite power structures and the centralisation of institutional authority.